2015
DOI: 10.1002/pat.3566
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, physico‐mechanical, and morphological properties of HDPE graft‐copolymerized with polystyrene

Abstract: In this study, polystyrene was graft‐copolymerized onto high‐density polyethylene (HDPE) by in situ polymerization of styrene monomer to change the physico‐mechanical and thermal properties of HDPE. The grafting was carried out in a Brabender‐type static mixer by injecting styrene monomer directly into the molten HDPE in the presence of a free‐radical initiator (lauroyl peroxide or LP). The effect of wt% of styrene and initiator concentrations on thermal, physico‐mechanical, and morphological properties of HDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Compared with pure PP, the crystallinity of each graft‐modified sample decreased, which is mainly caused by the amorphous structure of the St molecular chain and graft chain. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Compared with pure PP, the crystallinity of each graft‐modified sample decreased, which is mainly caused by the amorphous structure of the St molecular chain and graft chain. [ 33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Thomann et al found that in the case of SBS/PS blend, SBS with a substantial 'PS softening' effect was found to preferentially form elongated PB lamellar morphologies, which lead to increasing ductility [42]. On the other hand, several researchers reported that grafting of PS onto macromolecular chains of HDPE and polyurethane (PU) copolymer increased the tensile strength of HDPE and PU respectively [1,43]. It was also reported that the addition of a small amount of PP to LDPE in the presence of DCP increased the tensile strength of LDPE [44].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…to convert a low performing polymer into a high performing polymer. For example, the grafting of PS onto high-density polyethylene (HDPE) improves the tensile strength and decreases its hygroscopic expansion [1].…”
Section: Introductionmentioning
confidence: 99%